2002
DOI: 10.1037/0012-1649.38.5.749
|View full text |Cite
|
Sign up to set email alerts
|

The structure of language abilities at 4 years: A twin study.

Abstract: Normal language development was studied in 310 pairs of 4-year-old twins born in the United Kingdom in 1994. Twins were assessed individually in their homes on a diverse battery of language and nonverbal measures. Rotated factor analyses indicated the presence of a general Language factor (L) as well as a general Nonverbal (NV) factor. Moderate genetic influence was found for both L and NV abilities. Bivariate genetic analysis estimated a genetic correlation of .63 between L and NV abilities, implying that ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
84
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(98 citation statements)
references
References 36 publications
11
84
3
Order By: Relevance
“…The common loadings of measures of articulation and phonology on a single factor suggest that these deficits co-occur, at least during early childhood. Colledge et al (2002) reported that the GFTA and a nonword repetition task were highly correlated in a cohort of 4-year-old children and shared 62% of the reliable variance. The repetition of nonsense words is commonly thought of as a task assessing working phonological memory rather than speech production skills.…”
Section: Discussionmentioning
confidence: 99%
“…The common loadings of measures of articulation and phonology on a single factor suggest that these deficits co-occur, at least during early childhood. Colledge et al (2002) reported that the GFTA and a nonword repetition task were highly correlated in a cohort of 4-year-old children and shared 62% of the reliable variance. The repetition of nonsense words is commonly thought of as a task assessing working phonological memory rather than speech production skills.…”
Section: Discussionmentioning
confidence: 99%
“…TEDS has also investigated some less well-studied domains in early childhood, most notably language (e.g., Colledge et al, 2002;Viding et al, 2004). In the middle childhood years, TEDS has focused on learning abilities and disabilities, finding high heritability and moderate shared environmental influence in the first studies of early reading (Harlaar, Spinath, et al, 2005) and mathematics ; we are currently investigating writing and science.…”
Section: Univariate Resultsmentioning
confidence: 99%
“…Although cognitive and language data were obtained in TEDS at 2–4 years (e.g., Colledge et al, 2002; Dale et al, 1998; Dale, Dionne, Eley, & Plomin, 2000; Dionne, Dale, Boivin, & Plomin, 2003; Hayiou-Thomas et al, 2006; Kovas et al, 2005; Price, Dale, & Plomin, 2004; Spinath, Ronald, Harlaar, Price, & Plomin, 2003; Spinath, Harlaar, Ronald, & Plomin, 2004; Viding et al, 2003; Viding et al, 2004), the focus of this monograph is on learning abilities assessed at 7, 9, and 10 years. These ages correspond to the early school years during which important changes in academic content occur, reflected in the U.K. National Curriculum (NC) by a second key stage (see Appendices A–C).…”
Section: Methodsmentioning
confidence: 99%